Conflict Management and the Pursuit of Unity - Sohat, Fiolita; Weol, Wolter; Rampengan, Priscila Feibe (Peneliti.net, 2025)
Conflict within church organizations is both inevitable and multifaceted, often shaped by doctrinal differences, leadership styles, personal ambition, and external political dynamics. While typically perceived as negative, conflict—when managed wisely—can serve as a catalyst for spiritual growth and communal renewal. This study aims to explore how the theological principles in Philippians 2:2–4 offer a biblical foundation for conflict resolution and the pursuit of unity in ecclesial contexts. Employing a qualitative descriptive method with an exegetical approach, the research integrates textual interpretation with conflict management theory to construct a holistic model of reconciliation. The exegetical analysis reveals that values such as mutual love, humility, being like-minded, and prioritizing the interests of others are central to Paul’s vision of church unity. These values not only offer spiritual guidance but also shape practical strategies for conflict transformation within church communities. The findings affirm that biblical principles, when embodied in leadership and practice, can reduce polarization, strengthen internal relationships, and empower the church as an agent of reconciliation in wider society.